Information Technology: Impacts on Environment and Sustainable Development - Veeramani, S; Chowdhury, A.k. (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2015)
In this modern world, Information Technology gives impacts on society, countries, economy, and environment. This paper discusses the positive, negative, direct and indirect impacts of IT on environmental issues. A strategy for sustainable development in ICT and its future demand are also proposed. Apart from that, a research was also done to find a quantitative indicator to show the relationship between demand in IT industry and impacts to the environment. By using a mathematical formula, an estimation of the effect to the environment can be found. By using the indicator, it is hoped that society and the IT industry will become more aware of their action to the environment.